Developing a Framework for the Analysis of Program Notes Written for Contemporary Classical Music Concerts - Blom, Diana; Bennett, Dawn; Stevenson, Ian (Frontiers in Psychology, 2020)
At classical music concerts, a program note is the usual medium for communicating information about the music to be heard and performed. Although there may be crossover of information, the program note is distinct from the CD cover note, from notes contained within a musical score note, and from a composer’s directions for performers. With a focus on contemporary classical works in the Australian context, the researchers’ aim in this study was to develop and test an analytical frame of informational categories with which to examine program note content. Three extant studies—one scientific, one phenomenological and one semiotic—informed the development of an initial theoretical framework for program note analysis. This was tested through the analysis of program notes (n=30) from each of three writer cohorts: composers, professional writers, and higher education students. The analytical frame revealed different emphases of information categories among the three program note writer groups, with a more sophisticated combination of categories used by the professional writers and composers. This has implications for the teaching of program note writing in tertiary performance institutions, encouraging diversity of student content without extinguishing personal insights.